The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1958
DOI: 10.1084/jem.107.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Adenoviruses

Abstract: Investigation of the early period of viral multiplication permits observation of certain discernible stages in the reproductive cycle. Detailed analysis of these steps ((a) combination of virus with susceptible cells, (b) synthesis of new viral particles, and (c) dissociation or release of virus) yields data concerning basic characteristics of the agent. This information is pertinent for purposes of classification, and to stimulate hypotheses concerning the nature of the reactions of a virus with susceptible h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1959
1959
1968
1968

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Tissue Culture.--Epithelial cells of the HeLa strain (6) were employed in all experiments and were propagated in either Eagle's basal medium (7) containing 10 per cent human serum, or as previously described (8), in a growth fluid composed of 40 per cent human serum and Hanks' balanced salt solution.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tissue Culture.--Epithelial cells of the HeLa strain (6) were employed in all experiments and were propagated in either Eagle's basal medium (7) containing 10 per cent human serum, or as previously described (8), in a growth fluid composed of 40 per cent human serum and Hanks' balanced salt solution.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of virus used for infection of cultures in bottles and the time which elapsed between infection and harvest varied among the experiments; these data are included in the description of experiments. Infectivity titrations were performed in HeLa cell culture tubes using 1:3.2 (10 -0.5 ) serial dilutions; the details of the methods have been given elsewhere (8). Employing this titration procedure it has been shown that a difference of 0.36 log units between 2 infectivity titers should occur by chance only once in 20 titrations (8).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations